A muscular imprint on the anterolateral surface of the proximal femurs of the Krapina Neandertal collection. Issue 3 (19th January 2017) - Belcastro, Maria Giovanna; Mariotti, Valentina
Abstract: Objectives: The purpose of this study is to report and interpret a feature on the anterolateral surface of the proximal femurs of the Krapina hominid collection that we briefly described in 2006 ( Periodicum Biologorum, 108, 319–329). Materials and Methods: We recorded the presence or absence of the feature in all the proximal femurs of the Krapina collection (six specimens recordable) and in 622 modern human adult femurs. Results: The feature consists in a series of crests delimitating three raised or depressed areas. This feature has been found in three out of four adult Neandertal femurs observable. The two observable subadult Neandertal femurs do not show this character. None of the modern femurs displayed the feature. Conclusion: We interpret this feature as a muscular imprint, probably representing the m. vastus intermedius origin and discuss a possible interpretation. We did not find any other references for such imprint in the existing literature regarding the Neandertal femurs.